Computer Interactive Reminiscence and Conversation Aid groups—Delivering cognitive stimulation with technology. Issue 1 (5th September 2018) - Astell, Arlene J.; Smith, Sarah K.; Potter, Stephen; Preston‐Jones, Emily
Abstract: Introduction: Group‐based cognitive stimulation is the only nonpharmacologic intervention recommended by the UK National Institute for Clinical and Health Excellence for people with dementia. The potential of technology to extend the availability of group‐based cognitive stimulation has not been tested. Methods: One hundred sixty‐one people with dementia participated in an eight‐session group activity using Computer Interactive Reminiscence and Conversation Aid (CIRCA). Cognition, quality of life, and general health were assessed before intervention, postintervention, and 3 months later. Results: There was a significant improvement in cognition and quality of life at the end of the CIRCA group intervention, which was further improved at 3‐month follow‐up. Discussion: CIRCA group sessions improved cognition and quality of life similar to group‐based cognitive stimulation approved by the National Institute for Clinical and Health Excellence. These benefits were maintained at 3‐month follow‐up. The data confirm the potential of CIRCA, which can be populated with different cultural and language contents for different user groups.